Тенденції розвитку агробізнесу в Грузії: сучасні виклики та рішення - Kharaishvili, Eter; Suknishvili, Mirza (Dr. Viktor Koval, 2021)
Introduction. The article substantiates the importance of agribusiness development in solving the problem of food security and food security of the population. Economic indicators of agribusiness development in Georgia and Adjara region are analized, the role of determining agribusiness development trends and perspective directions in strengthening the rural community, especially in terms of rural community involvement in business is assessed. Therefore, in order to overcome the problem of agribusiness development, it is of special importance to study the development trends of agribusiness, to identify the current challenges in this field and to develop perspective directions of development. Aim and tasks. The aim of the research is to identify modern challenges based on the study of agribusiness development trends and to make recommendations on promising development directions. Results. The paper analyzes the views of researchers on alternative models of development in the field of agribusiness, focusing on the components of the agribusiness sector as a model. The article presents the conclusions and develops recommendations on overcoming the factors hindering the development of agribusiness and ways of future development. The development of the cooperation process is also important for the growth of scale and its place in international markets. Quantitative research has shown that 86% of farmers are not united in cooperatives. Even those who are united from year to year with less turnover of financial and material resources are recorded in the respective organizations, indicating their less life skills. Conclusions. Quantitative and qualitative research on the example of Adjara region (Georgia) has been conducted to identify the trends and characteristics of agribusiness development and to determine future directions. A questionnaire has been developed for the quantitative research and beneficiaries have been selected from the database of employees in the field of agribusiness, while for the qualitative research a group of experts has been identified and focus groups have been formed from these groups to clarify some problems. Quantitative research has identified the current challenges of agribusiness development, while qualitative research has identified the specific causes of the problems and the characteristics that will determine the future priorities of agribusiness development in the Adjara region.